A review of the genus Rhipidia Meigen from China, with descriptions of seven new species (Diptera, Limoniidae) - Zhang, Xiao; Li, Yan; Yang, Ding (Zootaxa, 2014)
The genus Rhipidia Meigen, 1818 from China is reviewed. Twenty-one species are presented, of which seven species, Rhipidia (Rhipidia) bilobata sp. nov., R. (R.) flava sp. nov., R. (R.) lobifera sp. nov., R. (R.) longa sp. nov., R. (R.) sejuga sp. nov., R. (R.) shennongjiensis sp. nov., and R. (R.) spinosa sp. nov., are described as new to science, and one species, R. (R.) reductispina Savchenko, 1983, is recorded from China for the first time. A key to the species of the genus Rhipidia from China is given.